A closed-loop self-righting controller for seated balance in the coronal and diagonal planes following spinal cord injury. (December 2020) - Bheemreddy, Akhil; Lombardo, Lisa M.; Miller, Michael E.; Foglyano, Kevin M.; Nogan-Bailey, Stephanie; Triolo, Ronald J.; Audu, Musa L.
Highlights: Self-righting controller using neuromuscular stimulation restores erect trunk posture. Controller worked for individuals paralyzed by various levels of spinal cord injury. External control unit used accelerometer-measured trunk tilt to regulate stimulation. One chest-worn sensor corrected posture deviations in coronal and diagonal planes. Controller assessed by response time, recovery time and percentage maximum deviation. Abstract: Spinal cord injury (SCI) often results in loss of the ability to keep the trunk erect and stable while seated. Functional neuromuscular stimulation (FNS) can cause muscles paralyzed by SCI to contract and assist with trunk stability. We have extended the results of a previously reported threshold-based controller for restoring upright posture using FNS in the sagittal plane to more challenging displacements of the trunk in the coronal plane. The system was applied to five individuals with mid-thoracic or higher SCI, and in all cases the control system successfully restored upright sitting. The potential of the control system to maintain posture in forward-sideways (diagonal) directions was also tested in three of the subjects. In all cases, the controller successfully restored posture to erect. Clinically, these results imply that a simple, threshold based control scheme can restore upright sitting from forward, lateral or diagonal leaning without a chest strap; and that removal of barriers to upper extremity interaction with the surrounding environment could potentially allow objects to be more readily retrieved from around the wheelchair. Technical performance of the system was assessed in terms of three variables: response time, recovery time and percent maximum deviation from erect. Overall response and recovery times varied widely among subjects in the coronal plane (415±213 ms and 1381±883 ms, respectively) and in the diagonal planes (530±230 ms and 1800±820 ms, respectively). Average response time was significantly lower ( p < 0.05) than the recovery time in all cases. The percent maximum deviation from erect was of the order of 40% or less for 9 out of 10 cases in the coronal plane and 5 out of 6 cases in diagonal directions. Graphical abstract: Image, graphical abstract